Analisis Sektor Unggulan Kota Serang Menggunakan Metode Location Quotient (LQ) dan Shiftshare - Anjani, Septi Rostika; Kusumaningsih, Asih; Lestari, Ambar Widya (LPPM University 17 Agustus 1945 Samarinda, 2025)
Economic growth is a benchmark for the success of development planning. Changes in sectors that increase or decrease are important in the development of a region. In the process of economic growth, a high level of structural and sectoral change will be seen related to this process. This research aims to analyze the leading sectors and economic structure in Serang City. The methods used are LQ and shiftshare analysis. This research uses secondary data obtained from the Central Statistics Agency. The results of the LQ calculation show that there are nine sectors which are the basic sectors, namely the Government Administration, Defense and Mandatory Social Security sectors with an average LQ value of 2.9, followed by the Accommodation and Food and Drink Provision sector, the Wholesale and Retail Trade sector, the Car and Bicycle Repair sector Motorcycles, Information and Communication sector, Education Services sector, Health Services and Social Activities sector, and Other Services Sectors. The results of the shiftshare analysis show that the GRDP contribution in the Wholesale and Retail Trade sector makes the largest contribution in Serang City, followed by the Construction sector and the Real Estate sector.